2016
DOI: 10.1530/rep-15-0471
|View full text |Cite
|
Sign up to set email alerts
|

Combined albumin and bicarbonate induces head-to-head sperm agglutination which physically prevents equine sperm–oviduct binding

Abstract: In many species, sperm binding to oviduct epithelium is believed to be an essential step in generating a highly fertile capacitated sperm population primed for fertilization. In several mammalian species, this interaction is based on carbohydrate-lectin recognition.D-galactose has previously been characterized as a key molecule that facilitates sperm-oviduct binding in the horse. We used oviduct explant and oviduct apical plasma membrane (APM) assays to investigate the effects of various carbohydrates; glycosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 79 publications
(109 reference statements)
2
24
2
Order By: Relevance
“…These residues were less highly expressed in the ampulla where cycle-related differences were observed, characterized by maximum galactosyl expression during oestrus (Ball et al 1997). Using an oviduct explant or apical plasma membrane model, we were unable to identify d-galactose as key molecule in equine sperm-oviduct interaction (Leemans et al 2016). Similarly, immunohistochemistry failed to reveal expression of d-galactose on the equine oviduct epithelial plasma membrane, whereas other galactosyl carbohydrates were present, which supported the findings of a previous study (Desantis et al 2004).…”
Section: Key Biochemical Factors In Equine Sperm-oviduct Bindingsupporting
confidence: 83%
See 2 more Smart Citations
“…These residues were less highly expressed in the ampulla where cycle-related differences were observed, characterized by maximum galactosyl expression during oestrus (Ball et al 1997). Using an oviduct explant or apical plasma membrane model, we were unable to identify d-galactose as key molecule in equine sperm-oviduct interaction (Leemans et al 2016). Similarly, immunohistochemistry failed to reveal expression of d-galactose on the equine oviduct epithelial plasma membrane, whereas other galactosyl carbohydrates were present, which supported the findings of a previous study (Desantis et al 2004).…”
Section: Key Biochemical Factors In Equine Sperm-oviduct Bindingsupporting
confidence: 83%
“…Although various carbohydrates, including galactosyl moieties, were highly expressed on the epithelium of oviduct explants, we were unable to competitively inhibit sperm-oviduct epithelium binding using any of a variety of candidate mono-and polysaccharides, including d-galactose, and lectins. We did, however, find that, in contrast to some other mammalian species (Suarez 2001), equine sperm-oviduct explant binding was neither dependent on calcium nor on disulphide (S-S) covalent bonds (Leemans et al 2016). In short, it appears that equine sperm-oviduct epithelium interaction in vivo is not based on a single lectin or S-S covalent bond.…”
Section: Key Biochemical Factors In Equine Sperm-oviduct Bindingcontrasting
confidence: 78%
See 1 more Smart Citation
“…The most notorious cytological effect of PKC activation with PMA is head-to-head agglutination with permanent flagellar motility, which provides clusters of sperm in motion (see video in Supporting information). Previous works have shown that sperm head-to-head agglutination occurs between spermatozoa with intact plasma acrosome membranes (Yang et al, 2012;Leemans et al, 2016). Moreover, Harayama et al (2003) showed that boar sperm agglutination is promoted by bicarbonate and PKA activation.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, they concluded that cytoplasmic free Ca 2+ is involved in sperm head-to-head agglutination and that agglutination is not the resultant of acrosome reaction (Harayama et al, 2003). Sperm head-tohead agglutination has been proposed to be an early stage of the capacitation process in vitro (Harayama et al, 2000), which physically prevents sperm from binding to the oviduct epithelium (Leemans et al, 2016). It is to note that flagellar activity is maintained, suggesting that the fluidity of the flagellar plasma membrane is not affected.…”
Section: Discussionmentioning
confidence: 99%